Values of fractional exhaled nitric oxide for cough-variant asthma in children with chronic cough - Zhou, Jing (J Thorac Dis, 2018)
BACKGROUND: Chronic cough is a common symptom in children. We wished to explore the value of fractional exhaled nitric oxide (FeNO) for cough-variant asthma (CVA) in children with chronic cough. METHODS: This prospective cohort study was conducted in the Children’s Hospital of Soochow University from January 2012 to December 2014. Children aged 6–14 years with a cough of duration >4 weeks were enrolled. They underwent FeNO measurement, sputum cytology and pulmonary function tests. RESULTS: A total of 115 patients and 25 healthy controls were evaluated. For the diagnosis of CVA, the optimal FeNO cutoff value was 25 ppb with a sensitivity of 84.0%, specificity of 97.1%, positive predictive value of 97.5%, and negative predictive of being 81.4%. The FeNO level had a significant correlation with eosinophil count in sputum (P<0.05). FeNO level in CVA was decreased significantly after treatment (P=0.001). CONCLUSIONS: In children, FeNO measurement might be an excellent method for diagnosing CVA with high sensitivity and specificity.